High myopia control is comparable between multifocal rigid gas-permeable lenses and spectacles - Yu, Li-hua; Zhuo, Ran; Song, Guan-xing; Lin, Meng; Jin, Wan-qing (Frontiers in Medicine, 2023)
Purpose Ocular pathology may be reduced by slowing myopia progression. The purpose of this study was to evaluate the potential of a novel custom-designed rigid gas permeable (RGP) contact lens to control high myopia by comparing the efficacy of multifocal RGP lenses and single-vision spectacles for high myopia control. Methods The medical records of children fitted with spectacles or multifocal rigid gas-permeable lenses between January 2018 and May 2020 were retrospectively reviewed. Children (5–17 years) with non-cycloplegic spherical equivalent refraction of ≤ −6.00 D or spherical equivalent refraction > − 6.00 D with baseline axial length ≥ 26.5 mm, and astigmatism of ≥ −2.00 D were included. Axial length and refraction were measured at baseline, before fitting the participants with multifocal rigid gas-permeable lenses or spectacles, and at 1- and 2-year follow-up visits. Changes in axial length were compared between the groups. Results Among the 77 children with 1-year follow-up data, the mean axial elongation was 0.20 ± 0.17 mm and 0.21 ± 0.14 mm in the multifocal rigid gas-permeable and control groups, respectively, without significant differences between groups (F = 0.004, p = 0.835). Among the 41 patients who completed 2 years of follow-up, the mean axial elongation values in the multifocal rigid gas-permeable and control groups were 0.21 ± 0.15 mm and 0.24 ± 0.13 mm, respectively, at the 1-year follow-up, and 0.37 ± 0.27 mm and 0.43 ± 0.23 mm, respectively, at the 2-year follow-up, without significant between-group differences at either time point (p = 0.224). Conclusion Axial length increased at a similar rate in both the control (spectacles) and multifocal rigid gas-permeable lens groups, suggesting that multifocal rigid gas-permeable lenses have no significant impact on controlling high myopia progression compared with spectacles.